Caracterização petrográfica e diagenética do Paleógeno da Bacia de São Paulo - Costa, Ana Carolina Alves da [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
A Bacia de São Paulo é uma pequena bacia paleógena localizada na porção sudeste do Estado de São Paulo, abrangendo parte significativa da Região Metropolitana de São Paulo. Este trabalho teve como objetivo principal aprofundar o conhecimento petrográfico das formações São Paulo e Resende, bem como sequenciar a evolução diagenética dos depósitos paleógenos da Bacia de São Paulo. Foram realizados estudos petrográficos qualitativos e semiquantitativos em amostras coletadas de duas extrações de areia e perfurações do Metrô, permitindo a individualização das formações e a identificação de uma sequência diagenética detalhada. Os resultados petrográficos indicam que os arenitos das formações São Paulo e Resende são classificados majoritariamente como arcóseos e subarcóseos, com diferenças texturais e composicionais significativas entre eles. A análise diagenética revelou que a bacia foi submetida a processos diagenéticos rasos e de baixa intensidade, sem evidências de condições de mesodiagênese ou telodiagênese. O presente estudo contribui para um melhor entendimento das características texturais e mineralógicas dos aquíferos que compõem a Bacia de São Paulo.

The São Paulo Basin is a small Paleogene basin located in the southeastern part of the State of São Paulo, extending along the Alto Tietê region and covering significant parts of the São Paulo metropolitan area. This study primarily aimed to increase the petrographic understanding of the São Paulo and Resende Formations, as well as to describe the diagenetic evolution of the São Paulo Basin as a whole. Qualitative and semi-quantitative petrographic studies were conducted on samples collected from two sand extractions and Metro drilling operations, allowing for the identification of the formations and the identification of a detailed diagenetic sequence. The results indicate that the sandstones of the São Paulo and Resende Formations can be petrographically classified mainly as arkosic and subarkosic, with significant textural and compositional differences between them. The diagenetic analysis revealed that the Basin underwent shallow and low-intensity diagenetic processes, with no evidence of mesodiagenesis or telodiagenesis conditions. The present study contribute to a better understanding of the textural and mineralogical characteristics of the São Paulo Basin aquifers.
Petrographic and diagenetic characterization of the Paleogene of the São Paulo Basin
Keywords: Bacia de São Paulo; Formação São Paulo; Formação Resende; Diagenesis; Eodiagênese; São Paulo Basin; São Paulo formation; Eodiagenesis